2017
DOI: 10.3390/molecules22040554
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transport Characteristics and Metabolism of C-Glucosyl Dihydrochalcone, Aspalathin

Abstract: Insight into the mechanisms of intestinal transport and metabolism of aspalathin will provide important information for dose optimisation, in particular for studies using mouse models. Aspalathin transportation across the intestinal barrier (Caco-2 monolayer) tested at 1–150 µM had an apparent rate of permeability (Papp) typical of poorly absorbed compounds (1.73 × 10−6 cm/s). Major glucose transporters, sodium glucose linked transporter 1 (SGLT1) and glucose transporter 2 (GLUT2), and efflux protein (P-glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…Notably, Huang et al [11] found that aspalathin absorption increased when present in green rooibos extract as opposed to the pure compound, indicating that other plant components present in the extract may assist in its transport across the membrane. In contrast, Bowles et al [10] found absorption of pure aspalathin to be similar to that when present in green rooibos extract. Experimental differences may account for this disparity in results, in particular the substantially higher aspalathin concentration, as well as the higher permeability of the monolayer used by Huang et al [11].…”
Section: Bioavailabilitymentioning
confidence: 86%
See 3 more Smart Citations
“…Notably, Huang et al [11] found that aspalathin absorption increased when present in green rooibos extract as opposed to the pure compound, indicating that other plant components present in the extract may assist in its transport across the membrane. In contrast, Bowles et al [10] found absorption of pure aspalathin to be similar to that when present in green rooibos extract. Experimental differences may account for this disparity in results, in particular the substantially higher aspalathin concentration, as well as the higher permeability of the monolayer used by Huang et al [11].…”
Section: Bioavailabilitymentioning
confidence: 86%
“…3) and thus also the whole dried shoots (4-10 %) [20]. Rooibos produced in the tradi- [7,8] Molecular weight 452.412 [7,8] Melting point 152-154°C [9] Polar surface area (Å 2 ) 208 [7] Log P (predicted) 2.07 [8] Log D (pH 7.4) (experimental) 0.13 [10] Log D (pH 5.5) (experimental) − 0.347 [11] H bond acceptors 11 [7,8] H bond donors 9 [7,8] Freely rotating bonds 6 [7,8] "Rule of 5′′ violations 2 [8] Solubility at pH 2 (µM) 153 [10] Solubility at pH 6.5 (µM) 123 [10] Solubility in FaSSIF at pH 6.5 (µM) 119 [10] ▶ Fig. 1 Commercial plantation of cultivated A. linearis (rooibos).…”
Section: Natural Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…While Stalmach et al [26], using high-performance liquid chromatography-mass spectrometry method, showed that O-methyl-aspalathin-O-glucuronide and eriodictyol-O-sulfate were the main metabolites excreted following ingestion of rooibos extract containing 10-fold higher levels of aspalathin in human subjects. In addition, a recent study by Bowles et al [27] showed that aspalathin can be absorbed and metabolized to mostly sulfate conjugates detected in the urine of mice. However, additional evidence is required to establish the pharmacokinetic profile of aspalathin.…”
Section: Aspalathinmentioning
confidence: 99%